Horizons of the sacred : Mexican traditions in U.S. Catholicism - Matovina, Timothy, 1955-; Riebe-Estrella, Gary, 1946- (Cushwa Center studies of Catholicism in twentieth-century America., 2002)
Horizons of the Sacred explores the distinctive worldview underlying the faith and lived religion of Catholics of Mexican descent living in the United States. Religious practices, including devotion to Our Lady of Guadalupe, celebration of the Day of the Dead, the healing tradition of curanderismo, and Good Friday devotions such as the Way of the Cross (Via Crucis), reflect the increasing influence of Mexican traditions in U.S. Catholicism, especially since Mexicans and Mexican Americans are a growing group in most Roman Catholic congregations. In their introduction, Timothy Matovina and Gary Riebe-Estrella analyze the ways Mexican rituals and beliefs pose significant challenges and opportunities for Catholicism in the United States. Original essays by theologians, historians, and ethnographers provide a rich interdisciplinary dialogue on how religious traditions function for Mexican American Catholics, revealing the symbolic world at the heart of their spirituality. The authors speak to the diverse meanings behind these ceremonies, explaining that Mexican American (and other Latino) Catholics use them to express not only religious devotion, but also ethnic identity and patriotism, solidarity, and, in some cases, their condition as exiles. The result is a multilayered vision of Mexican American religion, which touches as well on issues of racism and discrimination, poverty, and the role of women.